2005
DOI: 10.1051/0004-6361:20053365
|View full text |Cite
|
Sign up to set email alerts
|

Intergalactic HeII absorption towards QSO 1157+3143

Abstract: We report the discovery of a further line of sight allowing detection of He  Lyα absorption by the intergalactic medium. A HST/STIS survey of 32 bright z ∼ 3 quasars selected from the Hamburg Quasar Surveys yielded one detection toward QSO 1157+3143 (z ∼ 3, B 17). A 10 orbit follow-up spectrum reveals a UV spectrum significantly suppressed by two intervening Lyman limit systems at z = 2.77 and 2.94, but with the continuum flux recovering sufficiently shortward of ∼1700 Å to allow study of the He  absorptio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(74 citation statements)
references
References 24 publications
6
68
0
Order By: Relevance
“…Figure 14 plots τ eff,He ii from our simulations and from the most constraining observations, where τ eff,He ii is defined as minus the log of the He ii Lyα forest transmission. The square markers are from observations of quasars HS1700+6416 (Fechner et al 2006), HS1157+3143 (Reimers et al 2005), PKS1935−692 (Anderson et al 1999), Q0302−003 (Heap et al 2000), and SDSSJ2346−0016 . The vertical error bars on these measurements are just statistical, and the horizontal error bars signify the redshift range over which each of the values were estimated.…”
Section: Mean He II Lyα Forest Transmissionmentioning
confidence: 99%
“…Figure 14 plots τ eff,He ii from our simulations and from the most constraining observations, where τ eff,He ii is defined as minus the log of the He ii Lyα forest transmission. The square markers are from observations of quasars HS1700+6416 (Fechner et al 2006), HS1157+3143 (Reimers et al 2005), PKS1935−692 (Anderson et al 1999), Q0302−003 (Heap et al 2000), and SDSSJ2346−0016 . The vertical error bars on these measurements are just statistical, and the horizontal error bars signify the redshift range over which each of the values were estimated.…”
Section: Mean He II Lyα Forest Transmissionmentioning
confidence: 99%
“…While the detection of a high He II Ly-␣ optical depth was expected, the wide range in fluctuations in came as a surprise. Some of the systems indicate values as large as Ͼ 1000 at z Շ 3 based on follow-up optical observations of the H I Ly-␣ systems corresponding to the He II systems detected ͑Zheng, Reimers et al, 2005;Fechner et al, 2006͒. Combining N He II measurements from FUSE observations over the redshift range 2.30Ͻ z Ͻ 2.75 with measurements of N H I for the corresponding H I systems using Keck observation, Fechner et al ͑2006͒ obtained a very broad distribution for , as shown in Fig. 11.…”
Section: Constraints From Helium Ionizationmentioning
confidence: 99%
“…The measured values are well described by the model, except for a small tail at log 10 Ӎ 2.6. These values may be produced by patches of only partially ionized helium, as would remain during the epoch of He II reionization before its completion ͑Zheng, Reimers et al, 2005͒. Alternatively, they may result from local H I-ionizing sources reducing the H I column density, but not He II.…”
Section: Constraints From Helium Ionizationmentioning
confidence: 99%
“…As the reionization of the IGM is a gradual process, it is yet unclear when it started from a virtually neutral state. Indirect observational evidence (Theuns et al 2002;Zheng et al 2004b;Reimers et al 2005) suggests that the reionization of singly ionized helium started around z ' 3:4.…”
Section: Introductionmentioning
confidence: 99%